Motives for Playing Video Games in the Context of Time. Results of Empirical Research - Mazurkiewicz, Bartosz; Stefańska, Magdalena (Replay. The Polish Journal of Game Studies, 2021)
Video games are one of the most popular leisure activities. The multitude of games and ways of playing (individually, in a team, online, offline, etc.) allows players to meet their various needs. Thus, from the point of view of game developers, it becomes important to recognise these needs and adapt the product to the expectations of players. Taking the dynamic development of the video game market into account, it seems significant to recognise the players’ motives for spending their time on playing. Therefore, the aim of the article is to identify the players’ motives in terms of the type of need being met and to find an answer to the question whether there is a relationship between the time spent on games and the motives for playing (does the fact that we play longer change the type of need being satisfied?). The text refers to the results of research conducted in April 2020 on a sample of 2,527 players in Poland. The subjects of the study were people who actively played video games – every day or several times a week.